2017
DOI: 10.1037/ort0000254
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of a novel training program and use of psychiatric service dogs for military-related PTSD and associated symptoms.

Abstract: This study explored an intensive 3-week training program and use of psychiatric service dogs for military-related posttraumatic stress disorder (PTSD) and associated symptoms. The sample included 2 separate cohorts of military veterans (n = 7 and n = 5) with prior diagnoses of PTSD. Participants completed self-report measures assessing PTSD, depression, perception of social support, anger, and overall quality of life 1 month prior to the training (baseline), at arrival to the training site, and 6-month follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…This review demonstrated that there is relatively little empiric evidence available which supports the effectiveness of PSDs in the treatment of PTSD symptoms. Although it has been found that PSDs can positively influence perceived welfare and quality of life of those with PTSD (Kloep et al, 2017;Vincent et al, 2017;Yarborough et al, 2017), this evidence is mostly based on anecdotal reports and subject selfreport, making validity disputable. It does not explain to what extent the observed effect is influenced by the actual trained behaviour of the PSD, and to what extent by the inherent effects of human-animal interaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This review demonstrated that there is relatively little empiric evidence available which supports the effectiveness of PSDs in the treatment of PTSD symptoms. Although it has been found that PSDs can positively influence perceived welfare and quality of life of those with PTSD (Kloep et al, 2017;Vincent et al, 2017;Yarborough et al, 2017), this evidence is mostly based on anecdotal reports and subject selfreport, making validity disputable. It does not explain to what extent the observed effect is influenced by the actual trained behaviour of the PSD, and to what extent by the inherent effects of human-animal interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at current literature regarding PSDs, this statement holds true, as many studies on the effectiveness of PSDs show small sample sizes, a lack of control group, and no true randomization of research subjects. Some mention this lack as a constraint in their reporting, and Kloep, Hunter, and Kertz (2017) even names it as inherent to the research type. These factors are often absent because studies of PSDs necessarily depend on the availability of subjects with established PTSD, their willingness to participate, and the availability of service dogs.…”
Section: Best Practice For Psd Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Animals have been shown to provide therapeutic benefits to a variety of populations, including individuals with PTSD (Krause-Parello, Sarni, & Padden, 2016;Kloep, 2016;Kloep, Hunter, and Kertz, 2017). Using animals to assist veterans with PTSD is a topic of interest and may be an effective adjunct to standard treatment; however, several obstacles have hindered the advancement of this approach.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%